The first 8 months of COVID-19 pandemic in three West African countries: leveraging lessons learned from responses to the 2014–2016 Ebola virus disease outbreak. (8th September 2021) - Impouma, Benido; Williams, George Sie; Moussana, Fleury; Mboussou, Franck; Farham, Bridget; Wolfe, Caitlin M.; Okot, Charles; Downing, Katrina; Tores, Claudia Codeço; Flahault, Antoine; Pervilhac, Cyril; Ki-Zerbo, Georges; et al.
Abstract: Experience gained from responding to major outbreaks may have influenced the early coronavirus disease-2019 (COVID-19) pandemic response in several countries across Africa. We retrospectively assessed whether Guinea, Liberia and Sierra Leone, the three West African countries at the epicentre of the 2014–2016 Ebola virus disease outbreak, leveraged the lessons learned in responding to COVID-19 following the World Health Organization's (WHO) declaration of a public health emergency of international concern (PHEIC). We found relatively lower incidence rates across the three countries compared to many parts of the globe. Time to case reporting and laboratory confirmation also varied, with Guinea and Liberia reporting significant delays compared to Sierra Leone. Most of the selected readiness measures were instituted before confirmation of the first case and response measures were initiated rapidly after the outbreak confirmation. We conclude that the rapid readiness and response measures instituted by the three countries can be attributed to their lessons learned from the devastating Ebola outbreak, although persistent health systems weaknesses and the unique nature of COVID-19 continue to challenge control efforts.